Collaborative intimacies in music and dance : anthropologies of sound and movement - Chrysagis, Evangelos; Karampampas, Panas (Dance and performance studies ;, 2017)
Across spatial, bodily, and ethical domains, music and dance both emerge from and give rise to intimate collaboration. This theoretically rich collection takes an ethnographic approach to understanding the collective dimension of sound and movement in everyday life, drawing on genres and practices in contexts as diverse as Japanese shakuhachi playing, Peruvian huayno, and the Greek goth scene. Highlighting the sheer physicality of the ethnographic encounter, as well as the forms of sociality that gradually emerge between self and other, each contribution demonstrates how dance and music open up pathways and give shape to life trajectories that are neither predetermined nor teleological, but generative.